Destination image-satisfaction-loyalty paradigm of the world heritage sites in Malaysia - Guliling, Hasnawati (2018)
The tourism sector is experiencing a remarkable constant progress and becoming one of the fastest growing economic sectors globally. In this context, the image is an important element for the destination marketers to distinguish their destinations from others and to position themselves in this highly competitive industry. Therefore, it is high time for the academics and destination marketing organisations to undertake a dedicated study on destination loyalty. The study will gives a greater understanding of this concept and enhance their knowledge on the role of satisfaction in enhancing tourists’ loyalty. This study set out to test the Destination Image—Satisfaction—Loyalty Paradigm Model’s ability to explain tourists’ behaviors in reference to the United Nations Educational, Scientific, and Cultural Organisation (UNESCO) World Heritage Sites in Malaysia—namely, Melaka City, Melaka and George Town, Penang. It is anticipated that the model will enhance the understanding of image concept of tourism destinations in predicting tourists’ satisfaction and loyalty. The study is based on the deductive approach in which it is guided by theories or models. The theoretical framework of this study tested three components of destination image formation. In addition to the proposed components of cognitive and affective, this study also explores a new dimension, namely tourists’ emotional experience as a possible dimension. It could possibly lead to satisfaction and loyalty in the context of heritage tourism destinations in Malaysia. Furthermore, the present study is undertaken in order to fill the gap due to the limited studies and to assess the service quality performance in property and heritage attractions using the HISTOQUAL scale. The theoretical framework empirical assessment included a survey of four hundred and fifty (450) international and domestic tourists who visited both the heritage cities. Data are analyzed through multivariate analysis using Structural Equation Modelling (SEM) via the Analysis of Moment Structures (AMOS) software. The SEM technique is used to evaluate the causal model and the pooled confirmatory factor analysis is performed to examine the reliability and validity of the measurement model. The findings of this study provided valuable insights to the destination marketing organisations. First, the results indicated that the destination image impact is not limited to cognitive and affective evaluations. More importantly, the extant literature advanced more broadly with the addition of emotional experience aspect into the destination image formation and the interrelationships of the three components in one single model. Specifically, the findings revealed that significant relationships exist between the Destination Image constructs (Cognitive, Affective, and Emotional) and the major consequence constructs (Service Quality, Destination Satisfaction, and Destination Loyalty). The examples of supported relationships involving Destination Image constructs in this study include: Cognitive—Affective, Affective—Emotional, Affective—Service Quality, and Emotional—Destination Satisfaction. These relationships are major academic contribution in which they increase the knowledge of how the tourists perceived a particular destination and what constitutes destination image good predictors. Such understanding would assists the destination marketing organizations (DMOs) to design better marketing promotions in order to attract visitors as well as to encourage repeat visitors. In line with the aforementioned contribution, this study also supported the previous findings, which only consider Destination Image from the perspective of physical attributes to attract visitors to the destination; for instance, tangible resources (e.g. landscape, house, building and artifacts) and intangible resources (e.g. atmosphere and spirit). This study added tourists’ emotional experiences to the literature by providing empirical results from the heritage destination perspective. Next, as the empirical work involved examining the mediation effects of tourists’ satisfaction, this study revealed the presence of new empirical evidence. With regards to the relationship between Emotional and Destination Loyalty, the inclusion of Destination Satisfaction fully supports the mediating effect. This finding confirmed the underlying assumptions of marketing theory that customers’ favorable or unfavorable emotional responses will increase or decrease their satisfactory experiences, which eventually will affect their future intentions. Likewise, for the second relationship of Service Quality and Destination Loyalty, it is evidenced that tourists’ satisfaction mediates the relationship. Specifically, the result revealed that besides tourists’ emotional experience, service quality also has a substantial effect on tourists’ satisfaction and loyalty. In terms of practical implications, marketing campaigns should not emphasise solely on the destination distinguished characteristics; they should also accentuate the emotion aspect and strive to improve the quality of service. Various stakeholders are closely associated with Melaka City and George Town City (such as DMOs, private agencies, tour operators) through direct and indirect efforts; they should aggressively communicate about and collaborate with the UNESCO World Heritage Sites designation.